EKSPLORASI PERAN WORDWALL DALAM MENCIPTAKAN LINGKUNGAN BELAJAR IPAS YANG AKTIF DAN MENARIK - Naili Zakia; Eka Ramiati; Sudarsri Lestari; Vina Rohmatul Ummah (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Wordwall is a game-based digital learning medium with the potential to create a more active and engaging learning environment. This study aims to describe the role of Wordwall in fostering an active and engaging science and social studies (IPAS) learning environment for third-grade students at MI Tarbiyatul Athfal 1. The study employed a descriptive qualitative approach. The research participants included the IPAS teacher, third-grade students, and the school principal. Data were collected through observation, interviews, documentation, and technique triangulation, and were analyzed using the Miles, Huberman, and Saldana interactive model, consisting of data collection, data condensation, data display, and conclusion drawing. The findings indicate that Wordwall plays a significant role in increasing students' learning participation, creating a more engaging classroom atmosphere, and facilitating students' understanding of IPAS concepts through interactive learning activities. Furthermore, the successful implementation of Wordwall is supported by teachers' pedagogical competence and the availability of learning facilities at the school. These findings suggest that the effectiveness of Wordwall is influenced not only by the characteristics of the learning media itself but also by teachers' instructional strategies, students' active participation, and institutional support in creating an active, engaging, and meaningful learning environment.